2014
DOI: 10.1097/ccm.0000000000000046
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes, Predictors, and Prevalence of Anterior Pituitary Disorders Following Traumatic Brain Injury

Abstract: Approximately one third of traumatic brain injury patients have persistent anterior pituitary disorder. Older age, traumatic brain injury severity, and skull fractures predict anterior pituitary disorders, which in turn may be associated with higher ICU mortality. Further high-quality studies are warranted to better define the burden of anterior pituitary disorders and to identify high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 62 publications
1
35
0
5
Order By: Relevance
“…Investigators have found that younger women have better outcomes than do older women post-TBI; this may be attributable to the neuro-protective effects of hormones found in pre-menopausal women (Kirkness et al, 2004; Wagner et al, 2004; Ley et al, 2013). Despite conflicting results, researchers and clinicians alike are becoming aware of hormonal disturbances that often follow TBI (Ghigo et al, 2005; Schneider et al, 2011; Lauzier et al, 2014). Therefore, it is imperative for depression treatment care plans following TBI to be tailored to each gender specifically to address the physiological and hormonal differences between men and women who are affected by brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have found that younger women have better outcomes than do older women post-TBI; this may be attributable to the neuro-protective effects of hormones found in pre-menopausal women (Kirkness et al, 2004; Wagner et al, 2004; Ley et al, 2013). Despite conflicting results, researchers and clinicians alike are becoming aware of hormonal disturbances that often follow TBI (Ghigo et al, 2005; Schneider et al, 2011; Lauzier et al, 2014). Therefore, it is imperative for depression treatment care plans following TBI to be tailored to each gender specifically to address the physiological and hormonal differences between men and women who are affected by brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recently published systematic review of 66 studies (5,386 adult patients), the prevalence of persistent anterior pituitary hormone deficiencies was approximately 30% (11). Hypopituitarism was associated with higher mortality in the intensive care unit (ICU) in this analysis.…”
Section: Epidemiologymentioning
confidence: 81%
“…Hypopituitarism was associated with higher mortality in the intensive care unit (ICU) in this analysis. Older patients and those who have suffered skull-base fractures or more severe TBI appear to be at higher risk of hypopituitarism (11).…”
Section: Epidemiologymentioning
confidence: 99%
“…In contradistinction, the mean duration of coma in the group studied by Moreau et al was 17.7 days. 10 11 Although they did not address specific hormone deficits, they found that approximately 30% of subjects with a TBI had chronic PTH. Older age, skull fractures and the severity of the TBI were predictors of PTH.…”
Section: Incidencementioning
confidence: 98%